Control of electrical drives - Leonhard, Werner (Springer-Verlag, 1996)
Electrical drives play an important part as electromechanical energy converters in transportation, materials handling and most production processes. This book presents a unified treatment of complete electrical drive systems, including the mechanical parts, electrical machines, and power converters and control. Since it was first published in 1985 the book has found its way onto many desks in industry and universities all over the world. For the second edition the text has been thoroughly revised and updated, with the aim of offering the reader a general view of the field of controlled electrial drives, which are maintaining and extending their importance as the most flexible source of controlled mechanical energy.